Optimising combined open pit and underground strategic plan. (June 2013) - Roberts, B; Elkington, T; van Olden, K; Maulen, M
Abstract : This paper examines the case of a large open pit that is being planned at the site of an existing underground mine. Strategic planning work is undertaken to investigate the project value associated with an expansion of underground operations in conjunction with the proposed pit. Previous analysis by mine planners has determined that any depletion of the available open pit resource that changes the optimum pushback sequence will have a significant negative impact on overall project value. As a result, the main objective of this case study is to determine a strategic plan capable of yielding the optimum economic value for a combined underground–open pit operation. To investigate the viability of an underground expansion, a system to identify the stope resource that would add value to a combined operation if mined ahead of the pit is required. The main solution to this problem is the use of a resource model variable that defines the blocks which have greater discounted value if mined by stoping rather than by the open pit. From this potential underground resource, a series of mineable stope shells are generated at various cut-offs. This stope reserve data formed the input to an optimisation process used to optimise the underground mining plan, at a conceptual level, for various project configurations. Then, a dynamic programming mathematical program is used to evaluate the optimum value of a combined open pit and underground operation. The results generated in the case study presented herein provide a clear focus and direction for the next level of detailed mine design and planning.